The Yorùbá Social Values in Ọbasá’s Poetry - Saudat Adebisi Olayide Hamzat; Hezekiah Olufemi Adeosun (Yoruba Studies Review)
Among the social values which equip the Yorùbá person are honesty, transparency, accountability, integrity, justice, fair-play, family sense, hard work, and truthfulness. The basic values of the people determine their behavior and what they direct their energy toward. Yorùbá social values have received serious attention from scholars. However, the ideology that inform the social values have not been given a deserved attention. The main aim of this essay is to investigate the Yorùbá social values in Ọbasá’s poetry texts – Àwọn Akéwì I-III (1924, 1934, and 1945). The objective of the study is to examine the ideology which inform the social values, and which construct power. The paper also analyzes the extent to which the poet engages the ideology as exemplified in his poetry texts. In addition, the essay highlights the relevance of Ọbasá’s works to the contemporary Yorùbá society, and the literary devices employed by the poet to put across his message. The study employs descriptive and analytical methods using a New Historicism theory, which calls for a recovery of the ideology that gave birth to a text. The findings of this study reveal the Yorùbá philosophical thoughts on social values, and Obasa ͎’s interrogation of the phil ́ - osophical thoughts, which revere physical strength, wealth, position, children, 88 Saudat Adébísí O͎láyídé Hamzat & Hezekiah Olúfé͎mi Adeodun and knowledge as power. The study concludes that Ọbasá was a versatile and a thorough-bred poet whose poems call attention to the Yorùbá social values, to deconstruct and redefine power in a way that promote development. The study suggests that Ọbasá’s poems be studied holistically, and recommends that the poems should be reprinted and made available for scholarly work in institutions of learning.